Clinical characteristics, treatment, and outcomes of provoked acute cerebral sinovenous thrombosis in patients <21 years old: findings from the Kids-DOTT Multinational Trial - Gary M. Woods; Alexandra Miller; Maua Mosha; Christoph Male; Anupam Verma; Nicole Kucine; Christine Sabapathy; Kisha Beg; Sanjay Ahuja; Deepti Raybagkar; Kerry Hege; Clara Lo; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: Prospective multicenter data on the treatment and outcomes of children with cerebral sinovenous thrombosis (CSVT) are limited. We aimed to describe the clinical characteristics, treatment strategies, and outcomes of patients with a first-episode of provoked acute CSVT enrolled in the Kids-DOTT trial and compare these features with those of participants with non-CSVT venous thromboembolism (VTE). Methods: This was a subgroup analysis from the Kids-DOTT trial, a multinational randomized clinical trial on duration of anticoagulation for provoked acute VTE in patients younger than 21 years. Patient and thrombus characteristics, treatments, and outcomes of patients diagnosed with CSVT were compared with those of patients with non-CSVT VTE. Results: CSVT was diagnosed in 75 of the 532 (14%), 25 of whom received 6 weeks of anticoagulant treatment and 50 received 3 or more months. When compared with non-CSVT VTE, CSVT was more likely to occur in neonates and young children, associated with infection in general and acute head/neck infection in particular, and less likely to be related to central venous catheter. No patient in either group developed symptomatic recurrent VTE or clinically relevant bleeding, and there was no significant difference in rates of complete thrombus resolution between the 2 treatment durations. Conclusion: CSVT is most common in neonates and young children and those with acute head and neck infections. A 6-week anticoagulation treatment course appears to be safe (no clinically relevant bleeding) and effective (no difference in symptomatic recurrent VTE) for provoked acute pediatric CSVT. Nevertheless, given the nature of a subpopulation analysis, these findings should be interpreted with caution.